'Out-of-Africa' dispersal of tropical floras during the Miocene climatic optimum: evidence from Uvaria (Annonaceae) - Zhou, Linlin; Su, Yvonne C. F.; Thomas, Daniel C.; Saunders, Richard M. K. (Journal of biogeography, 2012)
Aim: African-Asian disjunctions are common in palaeotropical taxa, and are typically explained by reference to three competing hypotheses: (1) 'rafting' on the Indian tectonic plate, enabling Africa-to-Asia dispersal; (2) migration via Eocene boreotropical forests; and (3) transoceanic long-distance dispersal. These hypotheses are tested using Uvaria (Annonaceae), which is distributed in tropical regions of Africa, Asia and Australasia. Recent phylogenetic reconstructions of the genus show a clear correlation with geographical provenance, indicating a probable origin in Africa and subsequent dispersal to Asia and then Australasia.Ancestral areas and migration routes are inferred and compared with estimates of divergence times in order to distinguish between the prevailing dispersal hypotheses. Location: Palaeotropics. Methods: Divergence times in Uvaria are estimated by analysing the sequences of four DNA regions (matK, psbA-trnH spacer, rbcL and trnL-F) from 59 Uvaria species and 11 outgroup species, using a Bayesian uncorrelated lognormal (UCLD) relaxed molecular clock. The ancestral area of Uvaria and subsequent dispersal routes are inferred using statistical dispersal-vicariance analysis (S-DIVA). Results: Uvaria is estimated to have originated in continental Africa 31.6 Ma [95% highest posterior density (HPD): 38.4-25.1 Ma] between the Middle Eocene and Late Oligocene. Two main migration events during the Miocene are identified: dispersal into Madagascar around 17.0 Ma (95% HPD: 22.3-12.3 Ma); and dispersal into Asia between 21.4 Ma (95% HPD: 26.7-16.7 Ma) and 16.1 Ma (95% HPD: 20.1-12.1 Ma). Main conclusions: Uvaria fruits are widely reported to be consumed by primates, and are therefore unlikely candidates for successful long-distance transoceanic dispersal. The other biogeographical hypotheses, involving rafting on the Indian tectonic plate, and dispersal via the European boreotropical forests associated with the Eocene thermal maximum, can be discounted due to incongruence with the divergence time estimates. An alternative scenario is suggested, involving dispersal across Arabia and central Asia via the tropical forests that developed during the late Middle Miocene thermal maximum (17-15 Ma), associated with the ' out-of-Africa' dispersal of primates. The probable route and mechanism of overland dispersal between Africa and Asia for tropical plant groups during the Miocene climatic optimum are clarified based on the Uvaria data.